Parallel harmonic-oriented method for large-scale electric systems based on MPI programming and the limit cycle method - Garcia, N. (2005 IEEE Russia Power Tech, 2005)
An efficient harmonic-oriented method based on parallel processing and the limit cycle method to compute the periodic, steady-state solution of large scale electric systems is presented in this paper. The time domain numeric solution is based on Newton methods and the Poincare map to accelerate the convergence to the limit cycle. Furthermore, the implementation of parallel processing using MPI programming makes possible to speed up more the computations in the time domain. A three-phase version of the IEEE 118-node system is used to locate the limit cycle and study the transient response during a single-phase fault including a DVR-STATCOM. Simulations are implemented using a PC-Linux cluster with 856 processors. This approach allows the implementation of harmonic and power quality analyses, which help to understand the real impact of the operation of FACTS controllers on the power network.